2022
DOI: 10.5327/z2176-94781309
|View full text |Cite
|
Sign up to set email alerts
|

Use of Myriophyllum aquaticum to inhibit Microcystis aeruginosa growth and remove microcystin-LR

Abstract: Harmful algal blooms are one of the greatest challenges when preserving water sources, especially when involving cyanobacteria such as Microcystis aeruginosa. Finding remediation possibilities is needed, and one of them has been the use of macrophytes such as the species Myriophyllum, which have presented allelopathic mechanisms of phytoplankton control. Thus, this work aimed to evaluate the inhibition of M. aeruginosa cell growth in a co-exposure with Myriophyllum aquaticum and the influence on microcystin-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…The use of allelopathic applications from submerged aquatic macrophytes can be considered a promising strategy for controlling cyanobacteria. This technique is inspired by natural phenomena and offers a nature-based solution [15,18,24]. In this context, the use of the Myriophyllum genus is reported to show a higher presence of phenolic compounds in their phytochemical composition [22][23][24]26,36,37].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The use of allelopathic applications from submerged aquatic macrophytes can be considered a promising strategy for controlling cyanobacteria. This technique is inspired by natural phenomena and offers a nature-based solution [15,18,24]. In this context, the use of the Myriophyllum genus is reported to show a higher presence of phenolic compounds in their phytochemical composition [22][23][24]26,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…This technique is inspired by natural phenomena and offers a nature-based solution [15,18,24]. In this context, the use of the Myriophyllum genus is reported to show a higher presence of phenolic compounds in their phytochemical composition [22][23][24]26,36,37]. It has already been identified that phenolic compounds can be produced by macrophytes of this genus and may act as allelochemicals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations